HIV-related knowledge, information, and their contribution to stigmatization attitudes among females aged 15-24 years: regional disparities in Indonesia - Hidayat Arifin; Kusman Ibrahim; Laili Rahayuwati; Yusshy Kurnia Herliani; Yulia Kurniawati; Rifky Octavia Pradipta; Gevi Melliya Sari; Nai-Ying Ko; Bayu Satria Wiratama (BMC, 2022)
Abstract Background Stigmatization attitudes among youths toward people living with HIV (PLWH) is still an issue and concern in Indonesia. The purpose of this study was to determine the regional disparities, levels of HIV-related knowledge, information, and contributions related to stigmatization attitudes among females aged 15-24 years in Indonesia. Methods A cross-sectional study with The 2017 Indonesian Demographic Health Survey (IDHS) was used. A total of 12,691individual records of females aged 15-24 years were recruited through two-stage stratified cluster sampling. The endpoint was stigmatization attitude. Then, bivariate and multivariate binary logistics were performed. Results The findings showed that female youths who have no HIV-related knowledge (62.15%) and some source of information (52.39%). The highest prevalence of stigmatizing attitude was 59.82%, on Java Island. Multivariate analysis showed that females living in Sulawesi and Kalimantan; those living in a rural area; and those with more HIV-related knowledge were less likely to have a stigmatizing attitude. Conversely, females with the middle- to richest-wealth index and had some HIV-related information were more likely to have a stigmatizing attitude. Conclusion An understanding of stigmatizing attitudes should be considered through demographic factors, knowledge, and source of HIV-related information. The Indonesian government should pay more attention to indicators of HIV-related knowledge and information. Moreover, we suggest that the government collaborates with youths to disseminate information and restructure and reanalyze policies about HIV.